Integrasi Innovation dan Customer Relationship Dalam Meningkatkan Marketing Performance Melalui Competitive Advantage - Octavianus Sumardana Pratama; Made Mulia Handayani; Made Ayu Desy Geriadi; Cokorda Istri Agung Vera Nindia Putri (Widya Manajemen, 2026)
Craft products are export commodities that contribute to Bali's economic growth, but have experienced a decline in export value. The increasingly complex dynamics of the craft industry present various strategic challenges for craft businesses in Bali. Considering that craft products not only serve as a source of regional and national income but also constitute a cultural heritage, this requires attention. This study has theoretical innovations regarding the integration of innovation and relationship marketing as intangible resources from the RBV perspective. Furthermore, competitive advantage as a mediating variable in this relationship has rarely been studied specifically in the context of traditional craft products facing the global export market. In this context, Balinese craft businesses are required to increase their competitiveness through the implementation of sustainable innovation and strengthening relationships with customers as an effort to encourage improved marketing performance. This study involved all craft businesses in Bali as the population. The sample size was 96. Data were analyzed using PLS-SEM. The results of the study proved that innovation influences competitive advantage and marketing performance, but the effect was not significant on marketing performance, while customer relationships influenced competitive advantage and marketing performance. In this study, the competitive advantage achieved by Balinese craft businesses.